Should Warfarin and Heparins be Replaced by the New Oral Anticoagulants? - Farooq, M. S.; Farooq, M. Z.; Khan, S. (Drug Research, 2014)
The results of phase 3 clinical trials of the new oral anticoagulants portray them as a promising new class of drugs with potential to replace the conventional anticoagulants. However, the transition from conventional to new oral anticoagulants will be gradual because of the deep seated roots of the conventional drugs in clinical practice and the high cost of the new agents.